2011
DOI: 10.1097/qad.0b013e32834171f8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of central nervous system antiretroviral penetration on cognitive functioning in the ALLRT cohort

Abstract: Objective-Differences in antiretroviral (ARV) distribution into the central nervous system (CNS) may impact neurocognitive status. We assessed the relationship between estimates of ARV therapy penetration into the CNS, using a published ranking system, and neurocognitive status in HIV-positive subjects with plasma HIV-1 RNA (vRNA) suppression.Design-Subjects with ≥6 weeks ongoing ARV use and vRNA<50 copies/mL (N=2,636; 83% male, median baseline CD4 T-cells: 244 cells/uL) had ≥1 neuroscreen assessment (Trailmak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
2
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 24 publications
(28 reference statements)
2
137
2
1
Order By: Relevance
“…Most of the studies found a lower CSF HIV RNA with higher CPE score while the effect on immune-activation, MRI cerebral metabolites concentrations and neurocognitive testing were less concordant among studies: the results are summed up in table 2. [160][161][162][163][164][165][166][167][168][169][170][171][172] Furthermore while several retrospective studies found an association between higher CPE scores and lower CSF viral loads [153,154,[173][174][175] only one study (out of three) found a correlation with CSF escape. [21,143,176] Some reports tried to define a CPE cut off: respectively a value of 6 or 7 were found to be associated with heterogeneous CSF outcomes.…”
Section: The Cpe Scorementioning
confidence: 99%
“…Most of the studies found a lower CSF HIV RNA with higher CPE score while the effect on immune-activation, MRI cerebral metabolites concentrations and neurocognitive testing were less concordant among studies: the results are summed up in table 2. [160][161][162][163][164][165][166][167][168][169][170][171][172] Furthermore while several retrospective studies found an association between higher CPE scores and lower CSF viral loads [153,154,[173][174][175] only one study (out of three) found a correlation with CSF escape. [21,143,176] Some reports tried to define a CPE cut off: respectively a value of 6 or 7 were found to be associated with heterogeneous CSF outcomes.…”
Section: The Cpe Scorementioning
confidence: 99%
“…Furthermore, the raltegravir cerebrospinal fluid-to-plasma concentration ratio varies significantly between individuals (16-18), suggesting that its permeability across the blood-brain barrier may be dependent on the expression/activity of drug efflux transporters, such as P-gp or BCRP, at this blood-tissue barrier. Poor drug penetration into the CNS, a known sanctuary site for HIV-1 replication, has been linked to a suboptimal clinical response to ARV therapy and a decline in neurocognitive function (43,44). Although a recent study by Johnson et al (18) did not demonstrate a link between raltegravir cerebrospinal fluid concentrations and ABCB1 (P-gp) polymorphisms in healthy volunteers, this observation might be due to compensatory efflux mechanisms at the blood-brain barrier (e.g., BCRP-mediated efflux) or other interindividual differences that were not accounted for in this sample population (18).…”
Section: Figmentioning
confidence: 99%
“…This relationship, however, was not reported in patients using ART with three or less ARV drugs. 62 Better CNS-penetrating ART provides better control of viral replication within the CNS; however, HIV suppression below the levels of detection does not guarantee full cognitive recovery. 46 Interestingly, a study by Marra et al suggested that ARV drugs with good CNS penetration were associated with worse neurocognitive performance.…”
Section: Neuropsychiatric Effects Of Artmentioning
confidence: 99%